PENGARUH PELAKSANAAN PROMOSI DAN FASILITAS YANG DITAWARKAN TERHADAP MINAT BELI KONSUMEN (Studi Kasus Perumahan Villa Gardenia Tipe 75 PT. Bintang Properti Pekanbaru) - Siti Badingah; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In an increasingly competitive level, companies must be able to face competitors who offer similar products. Realizing that the company PT. Bintang Property has been prepared by conducting promotions and preparing adequate facilities to meet the needs and challenges needed by the people of Pekanbaru city.This study aims to determine the implementation of promotions and facilities offered, to determine consumer buying interest, and to determine the effect of promotion and facilities offered on consumer buying interest in Villa Gardenia housing type 75 at PT. Bintang Properti Pekanbaru. This research is descriptive quantitative with statistical calculation. Statistical analysis used in this research is multiple linear regression. Population in this research is resident of Villa Gardenia type 75 house as much as 150 KK. The sample used in this study taken 50% of the total population is set as many as 75 respondents.The results showed that the promotion of Villa Gardenia housing type 75 at PT. Bintang Properti Properties Pekanbaru is in the category "agree". This means that the implementation of this housing promotion is perceived by consumers is good. While the score of facilities offered on Villa Gardenia housing type 75 at PT. Bintang Properti Pekanbaru also in the category "agree". This means that the facilities offered by this company are perceived by consumers very well. Consumer buying interest in Villa Gardenia housing type 75 at PT. Bintang Properti Properties Pekanbaru is in the category "agree". This means that the products and facilities offered by the company are perceived by consumers very well. And after double linear regression testing is known that the implementation of promotions and facilities offered jointly significant effect on consumer buying interest in Villa Gardenia Housing Type 75 PT. Bintang Properti Pekanbaru.Keywords: Implementation of Promotion, Facilities, Consumer Buying Interest